Deteksi Dini Penyakit Degeneratif pada Lansia Melalui Kegiatan Pemeriksaan Kesehatan Gratis di Lingkungan Appassarenge Kelurahan Bentenge Kecematan Ujung Bulu Kabupaten Bulukumba - Herniyanti N; Nurul Hidayah Bohari; Lilis Qurani; Meri Karolina; Desi Ratnasari; Reny Sutriany (Masyarakat Mandiri : Jurnal Pengabdian dan Pembangunan Lokal, 2026)
Degenerative diseases are a major cause of morbidity in the elderly and continue to increase with age, lifestyle changes, and a lack of public awareness of the need for regular health check-ups. This community service activity aims to increase understanding and early detection of non-communicable diseases in people aged 30 years and older, particularly the elderly in the Appassarenge neighborhood, Bentenge Village, Ujung Bulu District, Bulukumba Regency. The activity methods included group exercise, blood pressure checks, blood sugar checks, health counseling, and referrals for participants with test results above normal limits. Data were analyzed descriptively to determine the proportion of participants with high blood pressure and blood sugar levels. The results showed that the majority of respondents had hypertension (70.97% of 31 participants), while 55.88% of 34 participants had high blood sugar levels. These findings indicate a high risk of non-communicable diseases in the elderly population related to diet, lack of physical activity, and a lack of regular health check-ups. This activity received a positive response because it provided easy access to health services and raised public awareness of the importance of early detection and adopting a healthy lifestyle. Overall, this community service activity contributed to increasing the elderly's knowledge and awareness of health, as well as supporting promotive and preventive efforts in preventing degenerative diseases.